Isolamento, determinação estrutural e atividades antitumoral e anti-inflamatória de triterpenos isolados de Vochysia cinnamomea (Vochysiaceae) - Lima, Rosa Silva (2010)
This work describes the study of plant extracts Vochysia cinnamomea Vochysiaceae, aiming to isolate and identify promising substances which has antitumor activities and anti-inflammatory properties. Extract of stem bark were isolated two triterpenes: lupeol and betulinic acid and a steroid: β-sitosterol. Extracts of the leaves were isolated three triterpenes: α-amyrin, β-amyrin and ursolic acid. The tests were carried forward to the antitumor cell lines MDA-MB-435 (melanoma), HCT-8 (human-colon) and SF-295 (central nervous system) with substances: Lupeol, betulinic acid, ursolic acid and mixing α and β amyrin showing no relevant activity. Triterpenes: lupeol and betulinic acid were tested for anti-inflammatory activity by the acetic acidinduced abdominal writhing method, but only the betulinic acid activity was satisfactory at a concentration of 30 mg / kg and Lupeol the concentration of 10mg/kg was inactive.